CULTIVATING SELF-CONFIDENCE: THE RELATIONSHIP BETWEEN PUBLIC SPEAKING AND STUDENTS INTRAPERSONAL INTELLIGENCE - Candra Kusuma; Ibrahim Besar (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study examines the relationship of intrapersonal intelligence on students public speaking skills. Communication is an essential aspect of life, especially in the context of education, particularly within educational settings, as it serves as a primary tool in the teaching and learning process. Public speaking, as a form of communication, plays a critical role in fostering self-confidence and enhancing social interaction among students. However, many students continue to face challenges in public speaking, often due to limited self-awareness and self-regulation, which is the most key component of intrapersonal intelligence. This study used a quantitative approach with a survey method, this study collected data through observation and the distribution of questionnaires to respondents. The results showed a positive and significant relationship between intrapersonal intelligence and students public speaking ability. This finding indicates that the higher the level of intrapersonal intelligence possessed by students tend to demonstrate greater proficiency in public speaking. Thus, the development of intrapersonal intelligence should be considered an integral part of the educational process in order to enhance students communication competencies.